Листи Миколи Макаренка до Данила й Вадима Щербаківських - Ходак, І. (Студії мистецтвознавчі, 2007)
The fact of loss of Mykola Makarenko’s (1877–1938) personal archive makes his epistolary heritage more valuable within the first steps on the way of the process of its systematization. We publish 6 letters addressed to famous researchers of the Ukrainian art Danylo and Vadym Scherbakivsky.